System Audit Information Service Public on Application Rage on Diskominfo Serang City Using Cobit 5.0 Framework - Maulida, Fadia Syifa; Auliana, Sigit; Permana, Basuki Rakhim Setya; Aryono, Gagah Dwiki Putra; Mansyuri, Umar (Indonesian Research Journal on Education, 2024)
Management technology good information​ now become need for all organization , good government nor private , for increase effectiveness And efficiency Work . Serang City Government , via Service Communication And Serang City Informatics , running mission This with optimizing e-government. In effort increase service public , Diskominfo develop application named​ RAGEM ( Religious , Adaptable, Great, Educate, Modern). This audit aim For know results evaluation And give recommendation related lack on system information RAGEM is used with uses a focused COBIT 5 framework in the APO11 (manage quality) domain and DSS02 (manage service requests). For get related audit results system the method used​​ on study This is qualitative with technique interview And observation . Results from system audits information This form capability level assessment as well findings And recommendation related lack on system RAGEM is running . With conducting a system audit information This so is known mark for APO11 domains amounted to 83.33% and DSS02 85.71% of system RAGEM This is at at level 3, which means the process has managed And documented.